Vital resonances encountering film with Varda, Haneke and Nancy - Hardy, Francesca Minnie (Edinburgh University Press, 2021)
Establishes resonance as a critical and conceptual paradigm for film analysis bringing together, for the first time, the work of three of the leading figures in European film: Agnès Varda, Michael Haneke and Jean-Luc Nancy.